Why reading is a challenge for U.S. L2 learners: The impact of cognitive, ecological, and psychological factors in L2 comprehension. (5th November 2019) - Sparks, Richard L.
Abstract: Studies have shown that U.S. learners' proficiency in reading and listening comprehension lags behind their ability to decode words. Recent studies have found that even after 3 years of high school L2 courses, U.S. students fail to develop minimal proficiency in reading comprehension. This paper suggests that while cognitive factors (word decoding and listening comprehension) explain the largest amount of variance in learners' ability to comprehend text, this model, known as the Simple View of Reading, does not consider other factors that may contribute to reading achievement, especially in a largely monolingual English context. In contrast, the Component Model of Reading posits that reading ability is influenced not only by cognitive skills but also by factors in the ecological and psychological domains. In particular, the U.S. social context hampers primarily monolingual English speakers from becoming proficient in L2 oral language and L2 reading comprehension. Pedagogical recommendations are offered. The Challenge: Cognitive factors in the Simple View of Reading, L2 word decoding, and L2 listening comprehension explain the largest amount of variance in L2 reading comprehension. But, do cognitive skills alone explain why U.S. L2 learners exhibit poor reading and language comprehension skills? This paper explores the ecological and psychological factors that contribute to L2 language comprehension in a monolingual environment.